Hollow Core-Shell Particle-Containing Coating for Passive Daytime Radiative Cooling. (July 2022) - Hu, Dandan; Sun, Shuai; Du, Peiyao; Lu, Xiaoquan; Zhang, Hui; Zhang, Zhong
Abstract: Passive daytime radiative cooling has received raising attention as a promising strategy for thermal management. Among various radiative cooling coatings, the particles-containing coating has a more practical application prospect because it can be produced on a large scale. Works on the investigation of the particle structure are still lack. Herein, hollow SiO2 @TiO2 core–shell particles (HCSP) and HCSP-containing silicone radiative cooling coating (RCC) were prepared. With stronger backscattering of HCSP, RCC reflected incident sunlight and emitted mid-infrared light efficiently, compared to the commercial white paint and hollow spheres coating, having the maximum Rsolar of 0.97 and maximum εATW of 0.95. It exhibited favorable cooling properties with a temperature drop of 5.26 °C illuminated under solar simulator and an average temperature drop of 6.9 °C simulated with COMSOL. RCC also showed good thermal insulation properties with a low thermal conductivity of 0.15 W·m −1 ·K −1 .